1998
DOI: 10.1038/bjc.1998.599
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and radiotherapy: (A) experience in patients undergoing treatment

Abstract: Summary Cancer patients undergoing radiotherapy frequently report fatigue. However, knowledge of the importance of fatigue for these patients and of the factors associated with their fatigue is limited. The aim of the current investigation was to gain more insight into fatigue as related to radiotherapy by answenng the following questions. First. how is the experience of fatigue best described? Secondly, to what extent is fatigue related to sociodemographic, medical (including treatment), physical and psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
126
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(139 citation statements)
references
References 18 publications
10
126
1
2
Order By: Relevance
“…This pattern is consistent with patterns reported in previous research. 36,37 Other treatment sites were not examined individually because of the effects of small sample sizes. Head and neck radiotherapy was associated with a lower level of fatigue at the initiation of treatment but a sharper increase in fatigue during treatment than noted with pelvic radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is consistent with patterns reported in previous research. 36,37 Other treatment sites were not examined individually because of the effects of small sample sizes. Head and neck radiotherapy was associated with a lower level of fatigue at the initiation of treatment but a sharper increase in fatigue during treatment than noted with pelvic radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…As was already found in earlier studies [29,30], extraversion and neuroticism were predictors of fatigue. Smets et al [25] suggested that the link between neuroticism and fatigue could be explained by Fig. 1 Course of fatigue over 6 months in women with benign breast problems or cancer the fact that individuals high in negative affect report more symptoms, probably due to their inner fixation and the tendency to interpret symptoms as threatening.…”
Section: Discussionmentioning
confidence: 99%
“…In general, BC patients are not as severely tired as chronic fatigue syndrome patients [24]: their fatigue is mainly mild to moderate [2]. However, fatigue might distress BC patients [25], reduce their quality of life (QOL) [29], and impair their physical activity [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among breast cancer patients and survivors, fatigue is strongly correlated with psychological distress and depression [11,13,18,19]. Depressed mood, pain, and sleep disturbance were the strongest correlates of fatigue in our large study of breast cancer survivors assessed at 1 Á5 years post diagnosis [13].…”
Section: Fatigue After Cancer and Its Treatmentsmentioning
confidence: 99%